Integrating field inventory and in silico phylogenetic analysis of pteridophytes at Gandul Mount, Indonesia - Candra, Sri Devi Galuh; Kinasih, Anggiresti; Khotimperwati, Lilih (Bioeksperimen: Jurnal Penelitian Biologi, 2026)
Pteridophytes are vascular plants that are considered the most primitive plants because they only use spores to reproduce. Several major fern families exhibit distinctive morphological and ecological characteristics that support their taxonomic recognition. Pteridophytes represent an important component of tropical biodiversity, yet their diversity and evolutionary relationships in karst ecosystems remain poorly documented. This study aimed to integrate field inventory and in silico phylogenetic analysis to assess pteridophyte diversity in Gandul Mount, Wonogiri, Central Java. Field data were collected using the cruise method, followed by morphological identification and habitat characterization. Phylogenetic relationships were inferred using matK gene sequences retrieved from the NCBI database and analyzed with the Maximum Likelihood method. The inventory recorded 17 species belonging to eight families, with Pteridaceae as the most dominant. Most species were lithophytic, indicating strong adaptation to rocky substrates. Two species were categorized as Least Concern, while the remaining species have not been evaluated by the IUCN. Eleven species showed ethnobotanical potential as medicinal plants, ornamentals, and phytoremediation agents. Phylogenetic analysis revealed clustering patterns consistent with taxonomic classification. These results demonstrate that Gandul Mount harbors considerable pteridophyte diversity and confirm that combining field-based inventory with in silico phylogenetic analysis provides a robust approach for biodiversity assessment and evolutionary interpretation.